What is the outlook for English councils' funding? - Kate Ogden; David Phillips (Institute for Fiscal Studies (IFS), 2024)
English councils saw big cuts to their funding during the 2010s, with spending on some services down between 40% and 70% over the decade. And although like virtually all public services, funding for local government was increased during the 2019-24 parliament, councils' finances are still under significant pressure. This reflects increases in demands and costs for key services that have often far outpaced economy-wide inflation, and has led to a growing number of councils requiring exceptional financial support. Despite this, the main parties' manifestos were virtually silent on their plans for council funding post-election. This means there is significant uncertainty about exactly what to expect over the next five years. This report therefore looks at a number of scenarios for councils' funding - and what these might mean for service delivery and financial sustainability given the spending pressures councils face. It finds that, given the current fiscal environment and overall spending plans implicit in the main parties' manifestos, cuts to some council services are highly likely unless spending pressures abate - even with big increases in council tax, and particularly in poorer parts of the country. There is also a real risk of significantly more councils being pushed to financial breaking point, joining the likes of Birmingham, Thurrock and Woking.
Keywords: 330; Government finances and spending; Distributional effects; Government spending; Local government finance; Public sector